Proteolysis-targeting chimeras: A promising technique in cancer therapy for gaining insights into tumor development. (28th July 2022) - Lv, Moyang; Hu, Weichao; Zhang, Shengwei; He, Lijiao; Hu, Changjiang; Yang, Shiming
Abstract: Proteolysis-targeting chimeras (PROTACs) are small molecules that specifically link E3 ubiquitin ligases to proteins of interest to mediate targeted ubiquitination and degradation. PROTACs are advantageous since they can target undruggable proteins with multiple domains, particularly those with smooth surfaces that lack a common binding domain for small-molecule inhibitors (SMIs). This review provides an overview of PROTAC technology and third-generation PROTAC development. We focused on designing and executing the most recent clinical trials involving PROTACs in cancer therapy. Additionally, we summarized novel findings regarding the mechanisms and signaling pathways involved in cancer development, such as the scaffolding function of certain proteins ignored by traditional SMIs and several recognized oncoproteins that participate in novel signaling pathways. We also discussed strategies for enhancing PROTAC antitumor activity and specificity. Highlights: The potent effect of PROTACs in inhibiting the function of target proteins. The latest clinical trails of PROTAC in prostate cancer and breast cancer. The superiorities of PROTACs to obtain insights into tumor development compared with traditional methods New Strategies to increase tumor specificity of PROTACS by photolabile caging group.